Skeletal Stability after Large Mandibular Advancement (> 10 mm) with Bilateral Sagittal Split Osteotomy and Skeletal Elastic Intermaxillary Fixation - Kristoffer Schwartz; Maria Rodrigo-Domingo; Thomas Jensen (eJournal of Oral Maxillofacial Research, 2016)
Objectives: The aim of the present study was to assess the skeletal stability after large mandibular advancement (> 10 mm) with bilateral sagittal split osteotomy and skeletal elastic intermaxillary fixation and to correlate the skeletal stability with the vertical facial type.